ANALISIS SOSIOLOGI HUKUM ATAS PENUNDAAN PEMBAGIAN WARISAN DALAM MASYARAKAT - Syeh Sarip Hadaiyatullah; Selly Marlina; Hifzhil Munadi; Lathifah Rambe (Yayasan Baitul Hikmah al-Zain, 2025)
The delay in the distribution of inheritance is a common social phenomenon in society and often leads to tension, injustice, and conflicts among heirs. This study aims to analyze the factors causing the delay in inheritance distribution and its socio-legal impacts using a sociological approach to law. The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation in one village in North Sumatra. The results of the study indicate that the delay in the distribution of inheritance is influenced by cultural factors, the dominance of certain parties within the family, a lack of understanding of inheritance law, and concerns about the breakdown of kinship relationships. The resulting impacts include inequality in access to rights, weakened social cohesion, and the absence of legal certainty regarding property ownership.